2021
DOI: 10.3390/jcm10040696
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient Age ≥80 Years on Postoperative Outcomes and Treatment Costs Following Pancreatic Surgery

Abstract: As life expectancy is increasing, elderly patients are evaluated more frequently for resection of benign or malignant pancreatic lesions. However, the impact of age on postoperative morbidity, mortality, and treatment costs in octogenarian patients (≥80 years) undergoing major pancreatic surgery needs further investigation. The clinicopathological data of patients who underwent pancreatic surgery between January 2015 and March 2019 in a major hepatopancreatobiliary center in Switzerland were assessed. Postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
3
0
2
Order By: Relevance
“…Despite the increased vulnerability of the very elderly population in the entire cohort, no difference was found for postoperative morbidity rate and severity These findings are in line with the pioneeristic study from Johns Hopkins University Hospital [24], that firstly demonstrated the safety and feasibility of PD in octogenarians, as well as with more recent experiences reported in the literature [9,10]. On the counterpart, some reports demonstrated statistically higher morbidity rates in aged groups compared to younger cohorts [11][12][13], and recognized increasing age as a risk factor for post-pancreatectomy onset of complications [39][40][41][42]. These contrasting data may reflect a difference in hospital volume for pancreatic surgery where the different studies were conducted.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Despite the increased vulnerability of the very elderly population in the entire cohort, no difference was found for postoperative morbidity rate and severity These findings are in line with the pioneeristic study from Johns Hopkins University Hospital [24], that firstly demonstrated the safety and feasibility of PD in octogenarians, as well as with more recent experiences reported in the literature [9,10]. On the counterpart, some reports demonstrated statistically higher morbidity rates in aged groups compared to younger cohorts [11][12][13], and recognized increasing age as a risk factor for post-pancreatectomy onset of complications [39][40][41][42]. These contrasting data may reflect a difference in hospital volume for pancreatic surgery where the different studies were conducted.…”
Section: Discussionsupporting
confidence: 83%
“…A recent epidemiological study found an age-specific trend towards an increase of PC diagnosis particularly in patients aged 80 years and over [21]. However, only a few studies specifically analyzed the outcomes of PD in the elderly population [10][11][12][13][22][23][24], and even less authors focused on octogenarians [9,11,25]. A few series recognized increasing age as a significant risk factor for a higher incidence of post-operative complications and mortality [26,27], while other authors demonstrated comparable short-term outcomes between octogenarians and younger patients after PD [9,10,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es ist unbestritten, dass ein Team, welches regelmässig onkologische Pankreasresektionen durchführt, besser gewappnet ist, auf anatomische Varianten, lokale Probleme oder auf postoperativ komplizierte Verläufe zu reagieren und Chirurgie-assoziierte Morbidität und Letalität tief zu halten. An der Universitätsklinik für Viszerale Chirurgie und Medizin betrug bei 125 Patienten unter 80 Jahren, die sich 1/2015 bis 3/2019 einer onkologischen Pankreasresektion unterziehen mussten, die Morbidität 20 % und die Letalität 2,4 % [17]. Ein hoher Qualitätsstandard lässt sich aber nicht durch eine einfache Mindestmengenvorgabe erreichen.…”
Section: Mindestfallzahlenunclassified
“…Die GABRINOX-Studie, eine Phase-II-Studie, evaluierte eine Therapie mit Gemcitabin und nab-Paclitaxel im 2-wöchentlichen Wechsel mit FOLFIRINOX. Die Gesamtansprechrate lag bei hohen 63,2 % (95 % KI 49,3-75,5 %) und das mediane Gesamtüberleben bei 17,8 Monaten (95 % KI 11,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]3), bei akzeptabler Toxizität [34] -ein weiterer interessanter Therapieansatz, der bis anhin aber noch keine Verwendung im klinischen Alltag findet.…”
Section: Palliative Chemotherapieunclassified